Analisis Pendapatan dan Strategi Bertahan Hidup Keluarga Petani Karet pada Masa Pandemi Covid-19 di Desa Pelajau Ilir Kecamatan Banyuasin III Kabupaten Banyuasin - Sriati, Sriati; Gunawan, Gunawan (Seminar Nasional Lahan Suboptimal, 2022)
Sriati S, Gunawan G. 2022. Income Analysis and Survival Strategies for Rubber Farming Families during the Covid-19 Pandemic in Pelajau Ilir Village, Banyuasin III District, Banyuasin Regency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 1057-1066. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Smallholder rubber plantations throughout South Sumatra are a source of livelihood for people in rural areas. The Covid 19 pandemic had an impact on the economy, including a decrease in rubber prices which had an impact on income. The objectives of this study were: (1) to analyze the income level of rubber farming families during the Covid-19 pandemic, compared to the poverty line limit set by BPS Banyuasin Regency, (2) identify the survival strategies of rubber farming families during the Covid-19 pandemic in Pelajau Ilir Village, and (3) analyze the relationship between the income level of rubber farming families and the survival strategies of rubber farming families during the Covid-19 pandemic in Pelajau Ilir Village. The research was conducted by survey method, with a sample of 66 people who were taken randomly from a population of 194 rubber farmers. The data were tabulated, analyzed descriptively, and Spearman Rank Correlation analysis. relationship between income and survival strategy. The results showed that the average income level per family member of rubber farmers was Rp. 846.813.00/capita/month, which was included in the category above the poverty line, which was Rp. 429.816.00/capita/month. There are 3 survival strategies carried out by rubber farming families during the Covid-19 pandemic, namely active strategies, passive strategies, and network strategies The average score of the total survival strategy was 11.65 (maximum score of 18) with moderate criteria. There is a relationship between the level of family income of rubber farmers with survival strategies carried out with a correlation coefficient of  Rs = 0.619* significant at  a = 0.05.